Diagnostic accuracy of the different pulse sequences of multi-parametric prostate MRI in the diagnosis of prostate cancer in the peripheral and transitional zones - Amr A. Elfattah Hassan Gadalla; Marianne Abdallah Sabet; Wael Abdelgawwad Edesa; Manal Halim Wahba; Sherif M. Abolyazid (The Egyptian Journal of Radiology and Nuclear Medicine, 2023)
Abstract Background One of the most prevalent malignancies among males is prostate carcinoma (PCa). For the diagnosis of PCa, multiparametric magnetic resonance imaging (mpMRI) constitutes by far the most accurate imaging technique. The PI-RADS v2.1 indications for dynamic contrast enhanced (DCE) sequence include identifying PI-RADS score 3 lesions, as clinically significant prostate carcinoma, aiding evaluation of examinations having poor quality of T2 as well as diffusion weighted imaging (DWI), and helping readers having relatively reduced expertise. Most articles don't provide outcomes pertaining to these indications, which weakens their conclusions. All MRI scans, even those with low quality T2 or DWI, were included in our study. Additionally, special emphasis on assessing peripheral zone lesions was made. Our objective was to assess the diagnostic accuracy of the various mpMRI pulse sequences, including the T2 sequence, diffusion and apparent diffusion coefficient (ADC) sequences, both T2 and diffusion sequences (biparametric (bp) MRI), DCE sequence, and the entire examination (mpMRI), in the diagnosis of PCa in the peripheral as well as the transitional zone using PI-RADS version 2.1 scoring system, once when malignant lesions are considered as those having PI-RADS scores 4 and 5 and once when PI-RADS categories 3, 4 and 5 were regarded as malignant. Results In the assessment of peripheral zone lesions, when PI-RADS categories 3, 4, and 5 were considered malignant, both bpMRI and mpMRI showed similar sensitivity (94.29%) and diagnostic accuracy (77.78%) while when considering scores 4 and 5 malignant, mpMRI demonstrated increased diagnostic accuracy and sensitivity but lower specificity (sensitivity was 82.86%/60%, specificity was 80%/100%, and diagnostic accuracy was 82.22%/68.89% for mpMRI/bpMRI test comparaison). Both bpMRI and mpMRI had similar sensitivity (95.83%) and diagnostic accuracy (71.05%) when PI-RADS categories 3, 4, and 5 were regarded as malignant; however, mpMRI demonstrated better diagnostic accuracy and sensitivity considering scores 4 and 5 malignant (sensitivity was 77.08% for mpMRI compared to 60.42% for bpMRI and diagnostic accuracy was 82.89% for mpMRI compared to 75% for bpMRI). Conclusions Both bpMRI and mpMRI demonstrated similar diagnostic accuracy when PI-RADS categories 3, 4, and 5 were taken into account as malignant while mpMRI had higher diagnostic accuracy considering categories 4 and 5 malignant.